A hierarchical porous N-doped carbon electrode with superior rate performance and cycling stability for flexible supercapacitors. (19th March 2018) - Cheng, Meng; Meng, Yuena; Meng, Qinghai; Mao, Lijuan; Zhang, Miao; Amin, Kamran; Ahmad, Aziz; Wu, Sixin; Wei, Zhixiang
Abstract : A novel all-carbon electrode with high N-doping content and a hierarchical porous structure was obtained successfully for high performance flexible supercapacitors. Abstract : A novel carbon electrode with high nitrogen content and a hierarchical porous structure has been prepared via a three-step carbonization of a three-dimensional graphene and polyaniline nanoarray composite film. The as-obtained nitrogen-doped electrodes show favorable features for flexible electrochemical energy storage, such as a hierarchical porous structure with interconnected three-dimensional (3D) pores, high flexibility and rich nitrogen-doping (9.71%). With respect to the multiple synergistic effects of these merits, a two-electrode-based supercapacitor has been fabricated. The assembled supercapacitor exhibited a high specific capacitance of 221 F g −1 at 5 mV s −1, and an excellent rate capability with a capacitance retention of 84% when the current density was varied from 3 A g −1 to 50 A g −1, and demonstrated no capacitance reduction even after 20 000 cycles of charging and discharging at 5 A g −1 . Moreover, when the electrode was assembled into a flexible device, it exhibited good flexibility with 96% retention of its initial capacitance after 10 000 cycles at 5 A g −1 when the flexible device was bent to 180°. The strategy in this study represents a facile strategy for constructing well-defined 3D structures with a high nitrogen-doping content, which is promising for constructing a flexible energy storage system.